Design for social innovation in Canada - Imbesi, Lorenzo (Common Ground Publishing, 2016)
Design has always played a role in the process of production, transformations in society and the economy, shifts in technology and impacts on the environment. The nature of the changes created by our post-industrial era is challenging the character of design and its role in society. The post-industrial era is creating complex projects for technology, service, systems, strategy and products. Clients are even becoming undefined stakeholders, and this can be extended to the entire community and the environment. The rise of digital technology and the knowledge society are introducing a new culture, which can be open, participatory, shared and collaborative. Here the designer is acting as a researcher, always questioning the character of the project, its outcomes and process. Open access, co-design, crowdfunding, digital manufacturing, open-source, DIY, enabling systems and networking can be included in the toolbox of the designer and can create opportunities to drive the change towards sustainability, equity and democracy. Social innovation is leveraging forms of collaboration and co-production in which designers, innovators, users and communities co-create knowledge and solutions for a wide range of social needs, exploiting the networking technologies. This book explores a number of areas where design can contribute to face the contemporary transformations in our society with real-life collaborative research and innovation projects. Through a number of Canadian social innovation case studies collected in social, environmental and technological fields, we recognize how the role of the designer cannot be limited to the production of finished objects; rather, designers can create tools and platforms to help users and citizens participate in projects, even allowing forms of personalization
Imprimé
Keywords: Canada; Innovation sociale